The Relationship Between Self-control and Cybersex in Adolescent Students at the University of TK - Tejo Kusumo, Andrianus; Tri Harsono, Yudi (KnE Social Sciences, 2022)
For some students, the internet is a place where they can consume sexual information freely. However, if sexual information is not properly consumed, this has a negative impact. The negative behavior of consuming sexual information through the internet is called cybersex. There are several factors for the emergence of cybersex in an individual, one of which is self-control. This study aimed to examine the relationship between self-control and cybersex in a group of students at the University of TK. Using the Snowballing Sampling-Quota Sampling technique, 60 students were included as respondents in this study. The data was collected using two scales, the self-control scale and the ISST scale. The self-control scale is based on Averril’s (1973) aspects, with a Likert scale model of 30 valid items (>30) and a reliability level of .925 according to Cronbach’s Alpha. The cybersex scale employs the ISST scale, which was adapted by Minenda et al. (2015) and retested on the subject of Malang city students by Agustina (2018), with 25 valid items (>30) and a reliability level (KR-20) of .857. The study’s results using Pearson’s product moment revealed a score of .027, indicating that there is a relationship between the two variables. The correlation value is -.286, indicating that there is a negative relationship between self-control ability and cybersex. Keywords: cybersex, self-control, adolescent, student